2007
DOI: 10.1002/qua.21400
|View full text |Cite
|
Sign up to set email alerts
|

A noteworthy feature of bond dissociation/formation reactions

Abstract: ABSTRACT:The reaction force F(R c ) of a process is the negative derivative of the potential energy V(R c ) of the system with respect to the intrinsic reaction coordinate R c . For the dissociation of a bond, F(R c ) has a negative minimum at a point R c ϭ ␣, while for the formation of the same bond, F(R c ) has a maximum at R c ϭ ␣. These extrema divide the respective processes into two phases. For the dissociation, these correspond to an initial stretching of the XOY bond (structural effect) followed by sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 15 publications
1
20
0
4
Order By: Relevance
“…has been amply used to understand several chemical reactions such as intra/intermolecular single and double proton transfers [15][16][17][18][19][20][21], conformational changes [22][23], bond-dissociation and bond-formation [24][25][26][27][28], S N 2 substitution [29][30], solvent effects [31][32], and catalysts [33][34][35].…”
Section: Test Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…has been amply used to understand several chemical reactions such as intra/intermolecular single and double proton transfers [15][16][17][18][19][20][21], conformational changes [22][23], bond-dissociation and bond-formation [24][25][26][27][28], S N 2 substitution [29][30], solvent effects [31][32], and catalysts [33][34][35].…”
Section: Test Casesmentioning
confidence: 99%
“…In 1999, the group of Toro‐Labbé [6] suggested the analysis of the reaction force (RFA) as a suitable tool for studying reaction mechanisms and identifying primitive processes in chemical reactions. The reaction force F ( ξ ), defined as the negative first derivative of the potential energy V ( ξ ) with respect to the reaction coordinate F()ξ=V()ξξ, has been amply used to understand several chemical reactions such as intra/intermolecular single and double proton transfers [15–21], conformational changes [22–23], bond‐dissociation and bond‐formation [24–28], S N 2 substitution [29–30], solvent effects [31–32], and catalysts [33–35].…”
Section: Test Casesmentioning
confidence: 99%
“…Once the chemical potential is known it is possible to evaluate the reaction electronic flux, J(n), (REF) as [30,31]:…”
Section: Energy and Reaction Forcementioning
confidence: 99%
“…They give an overview of halogen bonding [21]. Then they reported that analogous interactions are shown by atoms in Groups V and VI, and they have been compared quantitatively to hydrogen bonding [22][23][24][25]. Karpfen describes some calculations on BrF complexes with ammonia and amines [26].…”
Section: Introductionmentioning
confidence: 99%